Using the laws of logarithms, we can rewrite the equation as:
log3 𝑎 + log3 3^2 = log3 𝑏^3
Combining the logs on the left:
log3 (𝑎⋅3^2) = log3 𝑏^3
Setting the arguments equal:
𝑎⋅3^2 = 𝑏^3
Simplifying:
𝑎 = 𝑏^3/9
Therefore, the answer is A. 𝑎 = 𝑏3/9 or 𝑎 = 𝑏3.
If log3 𝑎 + 2 = 3log3 𝑏 , express 𝑎 in terms of 𝑏.
A. 𝑎 = 𝑏3
9
B.𝑎 = 𝑏3 − 9
C.𝑎 = 9𝑏3
D. 𝑎 = 𝑏3 − 3
3 answers
you should have stopped at a = b^3/9
That is NOT the same as b/3 !! Maybe you should not write "b3" if you mean b^3.
That is NOT the same as b/3 !! Maybe you should not write "b3" if you mean b^3.
I apologize for the confusion. You are correct. I will clarify that the answer is 𝑎 = 𝑏3/9, not 𝑎 = 𝑏/3. Thank you for bringing it to my attention.